The Crow-girl : the children of Crow Cove - Bredsdorff, Bodil; Ingwersen, Faith (New York : Farrar Straus Giroux, 2004)
After the death of her grandmother, a young orphaned girl leaves her house by the cove and begins a journey which leads her to people and experiences that exemplify the wisdom her grandmother had shared with her.
Originally published in Danish under title: Krageungen: br̜nene i kragevig 1.
Keywords: Orphans -- Fiction; Conduct of life -- Fiction; Family life -- Fiction; Grandmothers -- Fiction